One-step non-SUSY unification (1997)
ABSTRACT: We show that it is possible to achieve one-step gauge coupling unification in a general class of non-supersymmetric models which at low energies have only the standard particle content and extra Higgs fields doublets. The constraints are the experimental values of αem, αs and sin2θW at 102 GeV s, and the lower bounds for FCNC and proton decay rates. Specific examples are pointed out.